Associations between legal performance-enhancing substance use and future cardiovascular disease risk factors in young adults: A prospective cohort study - Nagata, J. M.; Ganson, K. T.; Cunningham, M.-L.; Mitchison, D.; Lavender, J. M.; Blashill, A. J.; Gooding, H. C.; Murray, S. B. (PLOS ONE, 2020)
Background: Legal performance-enhancing substances (PES), such as creatine, are commonly used by adolescents and young adults. As PES are mostly unregulated by the US Food and Drug Administration, there has been limited empirical attention devoted to examining their long-term safety and health outcomes. Preliminary studies have demonstrated associations between PES use and severe medical events, including hospitalizations and death. PES could be linked to cardiovascular disease (CVD), the most common cause of mortality in the US, by altering the myocardium, vasculature, or metabolism. The objective of this study was to examine prospective associations between the use of legal PES in young adulthood and CVD risk factors at seven-year follow-up.